Human acts a novel - Han, Kang 1970- (New York Hogarth, 2014)
Follows the aftermath of a young boy's shocking death during a violent student uprising as told from the perspectives of the event's victims and their loved ones.
When a young boy named Dong-ho is shockingly killed in the midst of a violent student uprising in South Korea, the victims and the bereaved encounter suppression, denial, and the echoing agony of the massacre. Through their collective heartbreak and acts of hope unfolds the tale of a brutalized people in search of a voice.
English translation of Korean title: Sonyæon i onda (The Boy is Coming)
This translation originally published, in slightly different form, in Great Britain by Portobello Books, London--Title page verso.
In English, translated from the Korean.
Keywords: Democratization -- Korea (South) -- History -- 20th century -- Fiction; Korea (South) -- Politics and government -- 1960- -- Fiction